PELATIHAN MEMBUAT LAPORAN KEUANGAN MASJID JAMIQ DESA PINTU PADANG KECAMATAN BATANG ONANG - siregar, erpiana (Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This PKM activity aims to socialize and train mosque administrators in regulating the financial administration of the Jamiq mosque in Pintu Padang village, especially in preparing mosque financial reports in accordance with PSAK No.45. The PKM method is carried out using the interview method to find problems in the field, the lecture method in socializing and introducing the basics of accounting, the tutorial method in preparing mosque financial reports. There were 20 participants who took part in this training. These participants were Jamiq Mosque administrators and mosque youth who were willing to take part in the training. This PKM activity will be held on Saturday, September 5 2022 from 08.00-12.30 WIB. The implementation of community service ran smoothly and received positive responses from various parties.